An English Teacher's Autobiography of Using Digital Multimodal Composing in Teaching Writing to Vocational Students - Wulan, Dyah Retno; Drajati, Nur Arifah; Supriyadi, Slamet (Universitas Sebelas Maret, 2022)
This study is an autobiography of the author's experience as an English teacher teaching 12th graders digital multimodal composing (DMC). I have been teaching vocational high school students for seventeen years in one of Indonesia's vocational high schools. I am still looking for the best way to develop the writing skills of vocational high school students. I want to alter their perceptions of writing. It is essential to create a fun and meaningful writing process both inside and outside the classroom. Students born in the twenty-first century, the digital generation, and modern students. DMC as the textual practice entails using digital tools to generate text by combining various semiotic modes. Each mode is meaningful and serves a purpose. As a teacher, I can create any digital mode based on my students' needs and knowledge. This study used the narrative inquiry method to explore and reflect on the story of the teacher.